Quality of life outcomes in colorectal cancer survivors: insights from an analytical study at a tertiary cancer center-Qatar - Adli, Nada; Ahmed, Mohammed Adil Arbab; AlMesbah, Nahla; Selim, Nagah; Ibrahim, Mohamed Abdelsalam Elimam; Awadelseed, Sujood Abdulwakeel Musa; Bougmiza, Ihab; Rasheed, Hadi Mohamad Abu; Rasul, Kakil (Frontiers in Oncology, 2026)
BackgroundColorectal cancer (CRC) is a major public health concern that affects patients’ quality of life (QoL) and imposes challenges on families and healthcare systems.ObjectivesTo assess QoL and its determinants among CRC patients in Qatar and identify sociodemographic and clinical factors influencing QoL in 2023.MethodsAn analytical cross-sectional study was conducted between July and December 2023. From the National Center for Cancer Care and Research (NCCCR) registry, 456 CRC patients were screened, and 169 eligible participants were included. QoL was evaluated using the EORTC QLQ-C30 and the CRC-specific QLQ-CR29 tools.ResultsMost patients were aged ≥45 years (80.5%), non-Qatari (79.9%), and married (88.8%). Hypertension (39.1%) and diabetes (31.4%) were the most common comorbidities. Adenocarcinoma was predominant (90.5%), with most cases diagnosed at advanced stages (III–IV, 74.8%) and metastasis in 71.6%. The sigmoid colon was the most common site (34.9%), and combined surgery and chemotherapy were the main treatments (69.2%). Global QoL was moderate to high (70.4 ± 18.5), with fatigue (23.9 ± 26.8) and financial difficulties (28.9 ± 40.4) as the most reported concerns. Functional QoL was higher among those with sufficient income (+12.5 points, p < 0.01) and longer time since diagnosis (+0.06 points/month, p < 0.05), but lower among those with higher education (–5.0 points, p = 0.05) or alcohol use (–11.2 points, p = 0.05).ConclusionsDespite advanced disease stages, CRC patients in Qatar reported good QoL. Socioeconomic status significantly influenced outcomes, highlighting the need for integrated psychosocial and financial support.